From bench to bedside: Developing CRISPR/Cas-based therapy for ocular diseases - Qing Zhao; Linxin Wei; Youxin Chen (Pharmacological Research)
Vision-threatening disorders, including both hereditary and multifactorial ocular diseases, necessitate innovative therapeutic approaches. The Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated protein (Cas) has emerged as a promising tool for treating ocular diseases through gene editing and expression regulation. This system has contributed to the development of representative disease models, including animal models, organoids, and cell lines, thereby facilitating investigations into the pathogenesis of disease-related genes. Besides, therapeutic applications of CRISPR/Cas have been extensively explored in preclinical in vitro and in vivo studies, targeting various ocular conditions, such as retinitis pigmentosa, Leber congenital amaurosis, Usher syndrome, fundus neovascular diseases, glaucoma, and corneal diseases. Recent advancements have demonstrated the technology's potential to restore cellular homeostasis and alleviate disease phenotypes, thereby prompting a variety of clinical trials. To date, active trials include treatments for primary open angle glaucoma with MYOC mutations, refractory herpetic viral keratitis, CEP290-associated inherited retinal degenerations, neovascular age-related macular degeneration, and retinitis pigmentosa with RHO mutations. However, challenges remain, primarily concerning off-target effects, immunogenicity, ethical considerations, and regulatory particularity. To reach higher safety and efficiency before truly transitioning from bench to bedside, future research should concentrate on improving the specificity and efficacy of Cas proteins, optimizing delivery vectors, and broadening the applicability of therapeutic targets. This review summarizes the application strategies and delivery methods of CRISPR/Cas, discusses recent progress in CRISPR/Cas-based disease models and therapies, and provides an overview of the landscape of clinical trials. Current obstacles and future directions regarding the bench-to-bedside transition are also discussed.